Shear capacity assessment of tuff panels strengthened with FRP diagonal layout - Marcari, Giancarlo (2011)
A quantitative analysis of the in-plane shear capacity of tuff masonry panels externally reinforced with FRP diagonal layout has been carried out. The objective is to provide a rational approach to the definition of the contributions from masonry and FRP to the lateral in-plane resistance of strengthened panels. Relevant experimental results of monotonic shear-compression tests are carefully analysed. A truss model approach, combined with a proper masonry strength criterion for masonry is proposed and validated. A comparison between computed and experimental data confirms the validity of the procedure in view of practical applications and code recommendations.